Heterosis in mild pungent chilli (Capsicum annuum L.) - B R Patel, A L Patel, K B Kathiria, (Journal of Spices and Aromatic Crops, 2014)
Field experiment was carried out to study heterosis for green fruit yield and its components of 28 F1 hybrids generated by half diallel crosses of eight diverse mild pungent chilli cultivars. Among 28 F1 hybrids, hybrids IVPBC-535 X SG-5, IVPBC-535 X ACS-03-14 and IVPBC-535 X ACS-03-13 were found to be most promising for green fruit yield and other desirable traits. Hence, they could be further evaluated to exploit the heterosis or utilized in future breeding programmes to obtain desirable segregants for the development of superior genotypes.